2014
DOI: 10.1155/2014/710791
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Pressure Pulsation and Rotating Stall Characteristics in a Centrifugal Pump with Slope Volute

Abstract: Unsteady flow structures can lead to severe vibration in centrifugal pump if the eigenfrequency of the rotor is equal to excitation frequency. In order to reduce rotor-stator interaction in centrifugal pump, a special slope volute was proposed. This paper explores the use of numerical simulation method to illustrate unsteady pressure pulsation and rotating stall characteristics under 0.05Φ -1.4Φ working conditions. Spectrums of pressure pulsation signals at different flow rates were analyzed. Relative velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Frequency domain analysis is mainly to transform the originally collected signal into frequency domain signal for analysis and processing through Fourier transform of the monitoring value of monitoring point, so as to quickly find the correlation between the collected signals. In time-domain analysis, the concept of pressure fluctuation coefficient is introduced in order to more intuitively reflect the change of pressure fluctuation at monitoring points and avoid the interference of static pressure value of monitoring points on the judgment of pressure fluctuation [34][35][36]. The formula is:…”
Section: Numerical Calculation and Analysis Methodsmentioning
confidence: 99%
“…Frequency domain analysis is mainly to transform the originally collected signal into frequency domain signal for analysis and processing through Fourier transform of the monitoring value of monitoring point, so as to quickly find the correlation between the collected signals. In time-domain analysis, the concept of pressure fluctuation coefficient is introduced in order to more intuitively reflect the change of pressure fluctuation at monitoring points and avoid the interference of static pressure value of monitoring points on the judgment of pressure fluctuation [34][35][36]. The formula is:…”
Section: Numerical Calculation and Analysis Methodsmentioning
confidence: 99%
“…The results ( 10 ) showed that the unsteady flow force exerted by the viscous force of the fluid on the impeller is related to the number of vanes and shows a star distribution. Zhang et al ( 11 ) found that, under rotating stall conditions, there are multiple viscous vortex structures in the impeller of the pump. These viscous vortex structures develop with the development of the rotating impeller.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative methods considering speed signals acquisition such as LDV [8], [12], or nonintrusive methods with accelerometers [11], have also been used for the identification of the phenomenon. Computational techniques such as CFD are being widely used in the characterization of this phenomenon in turbomachines [10], [15]- [17].…”
Section: Introductionmentioning
confidence: 99%